Inter‐Arm Blood Pressure Difference in Hospitalized Elderly Patients—Is It Consistent?. Issue 7 (30th May 2014) - Grossman, Alon; Weiss, Avraham; Beloosesky, Yichayaou; Morag‐Koren, Nira; Green, Hefziba; Grossman, Ehud
<x xml:space="preserve">Abstract</x> Inter‐arm blood pressure difference (IAD) is recognized as a risk factor for cardiovascular mortality. Its reproducibility in the elderly is unknown. The authors determined the prevalence and reproducibility of IAD in hospitalized elderly patients. Blood pressure was measured simultaneously in both arms on two different days in elderly individuals hospitalized in a geriatric ward. The study included 364 elderly patients (mean age, 85±5 years). Eighty‐four patients (23%) had systolic IAD >10 and 62 patients (17%) had diastolic IAD >10 mm Hg. A total of 319 patients had two blood pressure measurements. Systolic and diastolic IAD remained in the same category in 203 (64%) and 231 (72%) patients, respectively. Correlations of systolic and diastolic IAD between the two measurements were poor. Consistency was not affected by age, body mass index, comorbidities, or treatment. IAD is extremely common in hospitalized elderly patients, but, because of poor consistency, its clinical significance in this population is uncertain.